Peat ash and basic slag as substitutes for lime with reference to phosphorus uptake by turnip rape - Hartikainen, Helinä (Agricultural and Food Science, 1984)
The effect of peat ash and basic slag on the P supply to turnip rape was compared with that of calcitic and dolomitic limestone in a pot experiment performed with two acid mineral soils of pH 4.8 (CaCl2). Changes in soil properties induced by various liming agents were investigated in an analogous incubation test, and the results served to interpret the observations made in the pot experiment. When the liming materials were added in equal quantities, their ability to reduce soil acidity decreased in the sequence: calcite > dolomite > basic slag > peat ash. However, their growth-promoting effect appeared only in the second year and was not related to the neutralizing ability. In the muddy fine sand soil (3.0 % of org. C) poor in water-soluble P, the peat ash and basic slag were equally effective as calcite in increasing the dry matter yields. In the fine sand soil (6.4 % of org. C), the basic slag and dolomite significantly increased the second yield. The efficiency of peat ash and basic slag seemed to be attributable to their positive impact on P resources. In fact, peat ash served as a slowly acting P-fertilizer rather than as a liming agent. In the basic slag treatment, an increased silicate concentration obviously resulted in desorption of P. In the P-deficient muddy fine sand, the peat ash was equivalent to calcite in intensifying the P uptake. On the other hand, in the fine sand soil where the polymerization of Al due to an increased pH obviously resulted in enhanced P retention, the P uptake was higher in the soils treated with peat ash and basic slag than in those amended with conventional liming agents.